The Influence of Brand Ambassadors on Purchasing Decisions through Brand Image in the E-Commerce Industry - Sandriana Marina; Aisyah Rahmawati; Nadilla Elsa Deviyani; Chintya Devi (Jurnal Siber Multi Disiplin, 2026)
In Indonesia, technology is increasingly sophisticated, and the developing technology now causes the number of internet users to increase. The internet impacts people's behavior to shop online using e-commerce platforms. This study aimed to see the effect of brand ambassadors on purchase decisions through brand image on the marketplace platform. The principal data sources for this research, which employs a method that is quantitative, have been collected using online surveys. The data sample collected was 180 respondent from Gen Z in the DKI Jakarta area. The Accidental sampling method is used in the non-probability sampling method. In analyzing the data, also known as structural equation modeling, is used in this study to enable SMART PLS 3.0 software. The results of this study show that brand ambassadors have a positive effect on purchasing decisions mediated through brand image on the E-Commerce Platform.